2014
DOI: 10.1021/am504409q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, In Vitro Bioactivity, and Cellular Responses to a Polyetheretherketone Bioactive Composite Containing Nanocalcium Silicate for Bone Repair

Abstract: In this study, a nanocalcium silicate (n-CS)/polyetheretherketone (PEEK) bioactive composite was prepared using a process of compounding and injection-molding. The mechanical properties, hydrophilicity, and in vitro bioactivity of the composite, as well as the cellular responses of MC3T3-E1 cells (attachment, proliferation, spreading, and differentiation) to the composite, were investigated. The results showed that the mechanical properties and hydrophilicity of the composites were significantly improved by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 54 publications
7
83
0
Order By: Relevance
“…Our previous results 25,26 indicated that elastic modulus and compressive strength of the composite increased with increasing n-HA or n-CS content from 0 to 40 wt%, while the highest n-HA or n-CS content (60 wt%) yielded a lower elastic modulus and compressive strength, so the concentration of n-HA or n-CS in PEEK composite in this study was determined as 40 wt%. The 40 wt% n-HA/PEEK and 40 wt% n-CS/PEEK composites were fabricated using a compounding and injectionmolding technique according to our previously reported procedure, 25,26 and the pure PEEK sample was prepared using an injection-molding technique.…”
Section: Preparation Of Materialsmentioning
confidence: 79%
See 3 more Smart Citations
“…Our previous results 25,26 indicated that elastic modulus and compressive strength of the composite increased with increasing n-HA or n-CS content from 0 to 40 wt%, while the highest n-HA or n-CS content (60 wt%) yielded a lower elastic modulus and compressive strength, so the concentration of n-HA or n-CS in PEEK composite in this study was determined as 40 wt%. The 40 wt% n-HA/PEEK and 40 wt% n-CS/PEEK composites were fabricated using a compounding and injectionmolding technique according to our previously reported procedure, 25,26 and the pure PEEK sample was prepared using an injection-molding technique.…”
Section: Preparation Of Materialsmentioning
confidence: 79%
“…In addition, CS offers improved bioactivity compared with that of calcium phosphate materials. 18,19 In our previous study, 25 an apatite layer was formed on the n-CS/PEEK composite, and the entire surface of this specimen was nearly covered with a thick and compact apatite layer after immersion for 28 days. We predicted that apatite would form on the surface of n-CS/ PEEK in the early implantation period, and then, the bone matrix would integrate with the apatite.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The cell proliferation was expressed as relative proliferation rates, in which the modified ODs at day 3 and 5 were normalized to those at day 1 for each group. 20 2.5.3 Cell morphology. Cell morphology was visualized by detecting the filamentous actin of the cytoskeleton of MC3T3-E1 cells into scaffolds.…”
Section: Cell Culturementioning
confidence: 99%